Perception of and legal compliance with the law prohibiting cigarette sales to minors in Thailand following the raising of the minimum selling age to 20 years: a cross-sectional survey - Phetphum, Chakkraphan; Chomson, Supatana; Wangwonsin, Artittaya; Prajongjeep, Atchara; Keeratisiroj, Orawan (BMJ open, 2023)
ObjectivesThe minimum age for cigarette sales in Thailand was increased from 18 to 20 years, as stipulated in the Tobacco Products Control Act B.E. 2017. This study investigated tobacco retailers’ perceptions, cigarette sales behaviour and other factors relevant to selling cigarettes to people younger than 20 years in areas surrounding schools in Thailand.DesignCross-sectional survey.SettingTobacco shops within a radius of 500 m of secondary schools across four regions of Thailand. Data collection took place between May and August 2019.Participants1440 tobacco retailers (grocery or convenience stores) were sampled via a stratified, two-stage cluster sampling method. 1021 retailers completed the self-administered questionnaire.Outcome measuresTobacco sales to people younger than 20 years.ResultsThe prevalence of the retailers’ cigarette sales to youth younger than 20 years was 38.20% (95% CI 35.2% to 41.3%). Multivariable logistic regression analysis revealed associations with sale of single cigarettes (adjusted OR (AOR) 23.14, 95% CI 15.13 to 35.39), self-service sale of cigarettes (4.21, 2.59 to 6.86) and display of cigarettes at the point of sale (2.39, 1.47 to 3.89). Cigarette sales to underage youth were higher among retailers located in the northeast region (AOR 2.09, 95% CI 1.20 to 3.64) and among those who did not perceive the prosecution of violators in the past year (1.85, 1.16 to 2.96).ConclusionA large percentage of cigarette retailers violated the laws related to underage cigarette sales. Measures to minimise retailers’ legally non-compliant sales behaviours should be implemented along with improved legal enforcement.